Cities & the Sea Port City Planning in Early Modern Europe - Konvitz, Josef W. (Johns Hopkins University Press, 1978)
Originally published in 1978. Josef Konvitz provides a broad comparative study of European port cities since the Renaissance by examining how they were built and rebuilt in the context of urban industrialization. Konvitz argues that as seafaring became more critical to Western civilization, intellectuals and rulers placed more importance on urban planning. Planning looked different, of course, in various European cities. In Paris, riverside planning was patched into the existing frame of the city, whereas Scandinavian towns on the Baltic were over-designed to accommodate a degree of maritime trade unsustainable for cities writ large. In the eighteenth century, city planning fell out of vogue, and new solutions were introduced to help solve the problems created by urban development. With a series of helpful maps, Konvitz's book is an important source for urban historians of early modern Europe.